2018
DOI: 10.1093/jxb/ery004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high night temperature on storage lipids and transcriptome changes in developing seeds of oilseed rape

Abstract: High night temperature lowers the total fatty acids of seed and increases the proportion of 18-carbon unsaturated fatty acids by enhancing gibberellin signaling and the activity of the genes involved in fatty acid catabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 49 publications
1
35
0
3
Order By: Relevance
“…Using 10 years of field data and following a modelling approach, Baux et al (2013) observed an increase in oleic acid (C18:1) in conventional oilseed rape and high-oleic low-linolenic (HOLL) varieties associated with minimum temperature, coincided by a decrease in linoleic acid (C18:2) and linolenic acids (C18:3) concentration. In contrast, Zhou et al (2018) reported that HNT significantly decreased the total fatty acids and relative proportions of C18:0, C18:1, C20:1, in seeds of both low and high oil concentration cultivars but increased the proportions of C18:2 and C18:3 in both cultivars under HNT (19°C) compared to low night (9°C) temperatures. However, findings from our study revealed increased levels of saturated (C16:0 and C18:0) fatty acids without significant changes in unsaturated fatty acids (C18:1, C18:2, C18:3) except for C20:1 (Table 7).…”
Section: Hnt Alters Saturated Fatty Acids But Not Unsaturated Fattymentioning
confidence: 82%
“…Using 10 years of field data and following a modelling approach, Baux et al (2013) observed an increase in oleic acid (C18:1) in conventional oilseed rape and high-oleic low-linolenic (HOLL) varieties associated with minimum temperature, coincided by a decrease in linoleic acid (C18:2) and linolenic acids (C18:3) concentration. In contrast, Zhou et al (2018) reported that HNT significantly decreased the total fatty acids and relative proportions of C18:0, C18:1, C20:1, in seeds of both low and high oil concentration cultivars but increased the proportions of C18:2 and C18:3 in both cultivars under HNT (19°C) compared to low night (9°C) temperatures. However, findings from our study revealed increased levels of saturated (C16:0 and C18:0) fatty acids without significant changes in unsaturated fatty acids (C18:1, C18:2, C18:3) except for C20:1 (Table 7).…”
Section: Hnt Alters Saturated Fatty Acids But Not Unsaturated Fattymentioning
confidence: 82%
“…The glyoxylate cycle could influence the final lipid accumulation in the plant glyoxysome via peroxidation. Under other abiotic stresses, glyoxylate metabolism in the seeds of different B. napus lines was also found to change (Zhou et al ., ). The results of this study suggest that VOC plays a role in reducing ROS, which can lead to enhanced drought tolerance and lipid accumulation in B. napus .…”
Section: Discussionmentioning
confidence: 97%
“…Another cause could be the negative effect of high temperatures on photosynthesis and carbohydrate synthesis. Recently, Zhou et al (2018) specified that high heat stress during the night up-regulates lipases able to degrade storage lipids and fatty-acid desaturating enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the impact on seed yield and NUE of plants, environmental stresses affect seed composition. Several studies in rapeseed reported indeed that heat stress and drought decrease oil content and increase protein content of seeds ( Elferjani and Soolanayakanahally, 2018 ; Zhou et al , 2018 ). Moreover, together with the reduction of oil content, the composition of individual fatty acids in the seeds is altered under heat stress.…”
Section: Introductionmentioning
confidence: 99%